PENGARUH PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA - Purwanto, Kelik (J-MABISYA, 2020)
In this study, there are two variables, namely: the independent variable is the perception of price (X1) and service(X2) then the dependent variable is student satisfaction (Y). The research subjects were active students at theDharmas University of Indonesia and the research object was the Dharmas Indonesia University. The purpose ofthis study is to analyze the effect of perceived price and service quality on student satisfaction at Dharmas Universityof Indonesia. Indicators of perceived price (X1), affordability, price suitability while service (X2) are Tangible,Reliability, Responsiveress, Assurance, Empathy. and student satisfaction (Y), reliability, responsiveness, certainty,empathy, tangibility. The sample of this research is active students who study at the Indonesian DharmasUniversity. Then this research uses data collection techniques using a questionnaire, which is a data collectiontechnique carried out by giving a set of questions to other people who are respondents in the study, so that thatperson can provide answers to the questions given